Beyond all-or-nothing: why binary thinking undermines harm reduction in addiction medicine - Luke Manietta; William Drake (BJPsych Open)
In modern healthcare, decision-making favours neatly delineated, categorical imperatives. We prefer to say: ‘This practice is good’ and ‘That one is bad’, believing that each decision has a straightforward yes-or-no resolution. However, medicine thrives in uncertainty, partial improvements and small steps that can lead to life-altering gains. Harm reduction, whether for tobacco use, opioid dependence or beyond, embodies the acceptance of imperfect solutions. It is precisely in these areas that black-or-white thinking can be most destructive. Insisting on total cessation or complete eradication of risk, rather than supporting incremental progress, alienates many patients and perpetuates preventable morbidity and mortality. Recognising this pattern and transcending ‘all-or-nothing’ mindsets is crucial for compassionate, evidence-based care. Accordingly, we ask: ‘How does binary thinking in medical decision-making impact the effectiveness of harm reduction strategies?’ Such an inquiry addresses how well we can truly meet patient needs in real-world practice, especially amid complexity.